Investigating the Range of Symptom Endorsement at Initiation of a Graduated Return-to-Play Protocol After Concussion and Duration of the Protocol: A Study From the National Collegiate Athletic Association–Department of Defense Concussion, Assessment, Research, and Education (CARE) Consortium. Issue 6 (May 2020) - Brett, Benjamin L.; Breedlove, Katherine; McAllister, Thomas W.; Broglio, Steven P.; McCrea, Michael A.; ,; Hoy, April Marie (Reed); Hazzard, Joseph B.; Kelly, Louise A.; Port, Nicholas; Putukian, Margot; Pasquina, Paul; et al.
Background: Organizations recommend that athletes should be asymptomatic or symptom-limited before initiating a graduated return-to-play (GRTP) protocol after sports-related concussion, although asymptomatic or symptom-limited is not well-defined. Hypotheses: (1) There will be a range (ie, beyond zero as indicator of "symptom-free") in symptom severity endorsement when athletes are deemed ready to initiate a GRTP protocol. (2) Baseline symptom severity scores and demographic/preinjury medical history factors influence symptom severity scores at the commencement of the GRTP protocol. (3) Greater symptom severity scores at GRTP protocol initiation will result in longer protocol duration. (4) Symptom severity scores will not differ between those who did and did not sustain a repeat injury within 90 days of their initial injury. Study Design: Cohort study; Level of evidence, 2. Methods: Across 30 universities, athletes (N = 1531) completed assessments at baseline and before beginning the GRTP protocol, as determined by local medical staff. Symptom severity scores were recorded with the symptom checklist of the Sport Concussion Assessment Tool–3rd Edition. Nonparametric comparisons were used to examine the effect of medical, demographic, and injury factors on symptom endorsement at GRTP protocol initiation, as well as differences in symptom severity scores between those who did and did not sustain a repeat injury within 90 days. A Cox regression was used to examine the association between symptom severity scores at GRTP protocol initiation and protocol duration. Results: Symptom severity scores at the time when the GRTP protocol was initiated were as follows: 0 to 5 (n = 1378; 90.0%), 6 to 10 (n = 76; 5.0%), 11 to 20 (n = 42; 3.0%), and ≥21 (n = 35; 2.0%). Demographic (sex and age), medical (psychiatric disorders, attention-deficit/hyperactivity disorder, learning disorder), and other factors (baseline symptom endorsement and sleep) were significantly associated with higher symptom severity scores at the GRTP initiation ( P < .05). The 4 GRTP initiation time point symptom severity score groups did not significantly differ in total time to unrestricted RTP, χ 2 (3) = 1.4; P = .73. When days until the initiation of the GRTP protocol was included as a covariate, symptom severity scores between 11 and 20 ( P = .02; hazard ratio = 1.44; 95% CI, 1.06-1.96) and ≥21 ( P < .001; hazard ratio = 1.88; 95% CI, 1.34-2.63) were significantly associated with a longer GRTP protocol duration as compared with symptom severity scores between 0 and 5. Symptom severity scores at GRTP initiation did not significantly differ between those who sustained a repeat injury within 90 days and those who did not ( U = 29, 893.5; P = .75). Conclusion: A range of symptom severity endorsement was observed at GRTP protocol initiation, with higher endorsement among those with higher baseline symptom endorsement and select demographic and medical history factors. Findings suggest that initiation of a GRTP protocol before an absolute absence of all symptoms is not associated with longer progression of the GRTP protocol, although symptom severity scores >10 were associated with longer duration of a GRTP protocol. Results can be utilized to guide clinicians toward optimal GRTP initiation (ie, balancing active recovery with avoidance of premature return to activity).